Diffusion of chains in a periodic potential. (18th September 2017) - Terranova, G R; Mártin, H O; Aldao, C M
Abstract: We studied the diffusion of 1D rigid chains in a square wave potential of period T . We considered chains of type A (composed of N particles A) and chains of type A–B (composed of N /2 particles A and N /2 particles B). The square wave potential represents domains, a lamellar structure observed for block copolymers, in which the repulsive δ energy between each A particle (B particle) of the chain and B particles (A particles) of the medium where the chains diffuse. From Monte Carlo simulations and analytical results it is found that the normalized diffusivity D, for N ≪ T, presents a universal behavior as a function of X   =   Nδ for chains of type A and X   =  ( Nδ   −  ln T 2 ) for chains of type A–B, with and exponential decay for large values of X . For fixed values of δ and T, D is a periodic function of N with period T and 2 T for chains of type A and type A–B, respectively.